KAJIAN TEORI EKSISTENSI STATUS HUKUM TRANSEKSUAL TERHADAP PERUBAHAN JENIS KELAMIN PASCA PENETAPAN PENGADILAN - Andriyani, Agustini; Antasari, Rr Rina (Muamalah, 2019)
This study entitled the status of transsexual law after the court's determination of changes in sex and its implications for marriage law in the study of the theory of existence. This research is motivated by the condition of legal vacuum (rechtvacuum) of the provisions governing the legal status of transsexuals as well as special rules governing sex change for transsexuals. However, Article 56 paragraph (1) of Law Number 23 Year 2006 concerning Population Administration stipulates that the recording of other important events is carried out by Civil Registration Officers at the request of the concerned population after the determination of a district court that has obtained permanent legal force. Whereas what is meant by "other important events" are explained in the Elucidation of Article 56 paragraph (1) of the Population Administration Law as follows: "What is meant by" other important events "are events determined by the district court to be recorded at the Implementing Agency, including changes in types sex".